Coordinated German Internationalization: Broadening Perspectives - Streitwieser, Bernhard; Olson, Jennifer; Burkhart, Simone; Klabunde, Niels (International Higher Education, 2015)
This discussion addresses the changing policy landscape of German higher education, including a shift from development aid to a focus on competition and highly skilled migration; changes in student mobility patterns; and goals and priorities at the federal, state, and institutional levels that have supported internationalization efforts. The discussion concludes with a brief look at anticipated financial and thematic challenges.